The rapid and precise computation of GPS slant total delays and mapping factors utilizing a numerical weather model. Issue 3 (24th March 2014) - Zus, Florian; Dick, Galina; Douša, Jan; Heise, Stefan; Wickert, Jens
<x xml:space="preserve">Abstract</x> In a previous study we developed an elegant technique to compute the signal travel time delay due to the neutral atmosphere, also known as slant total delay (STD), between a Global Positioning System (GPS) satellite and a ground‐based receiver utilizing data from a numerical weather model (NWM). Currently, we make use of NWM data from the Global Forecast System (GFS) because short‐range forecasts are easily accessible. In this study we introduce some modifications which double the speed of our algorithm without altering its precision; on an ordinary PC (using a single core) we compute about 2000 STDs per second with a precision of about 1 mm. The data throughput and precision are independent of the vacuum elevation (azimuth) angle of the receiver satellite link. Hence, the algorithm allows the computation of STDs in a mesobeta‐scale NWM with an unprecedented speed and precision. A practical by‐product of the algorithm is introduced as well; the Potsdam Mapping Factors (PMFs), which are generated by fast direct mapping utilizing short‐range GFS forecasts. In fact, it appears that the PMFs make the application of parameterized mapping in GPS processing obsolete.